2010
DOI: 10.1075/idj.18.2.04ens
|View full text |Cite
|
Sign up to set email alerts
|

Rhetorical figures in TV commercials: The occurrence of schemes and tropes and their effects on commercial likeability

Abstract: Studies on print advertising have demonstrated that the use of rhetorical devices enhances ad likeability (e.g., Van Enschot, Hoeken, & Van Mulken, 2008). In this study, content analysis data are mapped to real consumer response data obtained from a sample of 199 real-life TV commercials. The content analysis showed that schemes and tropes occur in almost all TV commercials, in the verbal, visual and verbopictorial mode. Tropes occur most often. Above this, commercials with tropes are liked better than commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Multiple advertising studies, for instance, have also observed a nondistinctive use of visual rhetoric in U. K.-based and Dutch-based texts (Odekerken-Schröder, De Wulf, & Hofstee, 2002;van Enschot, Beckers, & van Mulken, 2009). Our second research objective was to explore whether local culture is reflected in the pictures included in these management statements.…”
Section: Discussionmentioning
confidence: 98%
“…Multiple advertising studies, for instance, have also observed a nondistinctive use of visual rhetoric in U. K.-based and Dutch-based texts (Odekerken-Schröder, De Wulf, & Hofstee, 2002;van Enschot, Beckers, & van Mulken, 2009). Our second research objective was to explore whether local culture is reflected in the pictures included in these management statements.…”
Section: Discussionmentioning
confidence: 98%
“…Rhetorical figures (schemes, tropes) can also help to make sense of the effectiveness of early iPhone advertising. Research on rhetorical figures has linked people's enjoyment of deviations from "expected" language (e.g., use of alliteration and rhyme) and cleverness in expression (e.g., puns, metaphors) with a liking of the product being advertised (van Enschot, Beckers, & van Mulken, 2010;van Enschot & Hoeken, 2015). The effectiveness of the advertising that draws upon rhetorical figures seems to be the positive feelings that people have when they "decipher" the messages associated with the product being advertised.…”
Section: Apple's Storiesmentioning
confidence: 99%
“…The occurrence and impact of rhetorical figures have been studied mainly within the context of print advertising. However, Van Enschot, Beckers, and van Mulken (2010) show that the vast majority of television commercials contains tropes as well. Interpreting tropes in commercials may be more difficult because commercials contain more tropes as well as multimodal information.…”
Section: Renske Van Enschot and Hans Hoekenmentioning
confidence: 99%
“…The studies discussed previously have all focused on the use of tropes in print advertising. Van Enschot, Beckers, and van Mulken (2010) show that tropes are a popular ingredient of television commercials as well. Approximately 82% of the commercials analyzed contained at least one trope.…”
mentioning
confidence: 99%